Detecting discrete spatial heterogeneity in compositional data via generalized group minimax concave penalty regularization - Ryo Inoue; Masato Ishikawa; Zhan Peng (Spatial Statistics, 2026)

Design of a novel tracked seabed exploration vehicle endowed with a non-compliant passive suspension system - Enrico di Maria; Yosaku Maeda; Masato Ishii; Tomoya Inoue (Ocean Engineering, 2026)

Real-time optimal control allocation for underwater vehicle with non-convex dead-zone constraints - Yuhei Noborio; Yosaku Maeda; Hitoshi Kakami; Masato Ishii; Tomoya Inoue; Atsuo Maki (Ocean Engineering, 2026)

Organ-specific proteomic responses to tetrodotoxin administration in the liver and skin of Takifugu rubripes - Natsuki Ono; Ryohei Tatsuno; Emiko Koba; Takeshi Bamba; Yuki Takai; Abrianna Elke Chairil; Zhaoya Li; Shoma Inoue; Hayato Kimura; Kazuma Kitamura; Masato Honda; Kenichi Yamaguchi; et al. (Toxicon, 2026)

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Consensus Paper: Models of Cerebellar Functions - Shinji Kakei; Andreea C. Bostan; Timothy J. Ebner; Mohammad Amin Fakharian; Hiroaki Gomi; Xavier Guell; Marie Hemelt; Huu Hoang; Court Hull; Masato Inoue; Takahiro Ishikawa; Masashi Kameda; et al. (The Cerebellum, 2026)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Genetic landscape in undiagnosed patients with syndromic hearing loss revealed by whole exome sequencing and phenotype similarity search - Hideki Mutai; Fuyuki Miya; Kiyomitsu Nara; Nobuko Yamamoto; Satomi Inoue; Haruka Murakami; Kazunori Namba; Hiroshi Shitara; Shujiro Minami; Atsuko Nakano; Yukiko Arimoto; Noriko Morimoto; et al. (Human Genetics, 2025)

Effects of different combinations of mechanical loading intensity, duration, and frequency on the articular cartilage in mice - Yoshio Wakimoto; Yasushi Miura; Shota Inoue; Masato Nomura; Hideki Moriyama (Molecular Biology Reports, 2024)
Background Understanding how healthy articular cartilage responds to mechanical loading is critical. Moderate mechanical loading has positive effects on the cartilage, such as maintaining cartilage homeostasis. The degree of mechanical loading is determined by a combination of intensity, frequency, and duration; however, the best combination of these parameters for knee cartilage remains unclear. This study aimed to determine which combination of intensity, frequency, and duration provides the best mechanical loading on healthy knee articular cartilage in vitro and in vivo. Methods and results In this study, 33 male mice were used. Chondrocytes isolated from mouse knee joints were subjected to different cyclic tensile strains (CTSs) and assessed by measuring the expression of cartilage matrix-related genes. Furthermore, the histological characteristics of mouse tibial cartilages were quantified using different treadmill exercises. Chondrocytes and mice were divided into the control group and eight intervention groups: high-intensity, high-frequency, and long-duration; high-intensity, high-frequency, and short-duration; high-intensity, low-frequency, and long-duration; high-intensity, low-frequency, and short-duration; low-intensity, high-frequency, and long-duration; low-intensity, high-frequency, and short-duration; low-intensity, low-frequency, and long-duration; low-intensity, low-frequency, and short-duration. In low-intensity CTSs, chondrocytes showed anabolic responses by altering the mRNA expression of COL2A1 in short durations and SOX9 in long durations. Furthermore, low-intensity, low-frequency, and long-duration treadmill exercises minimized chondrocyte hypertrophy and enhanced aggrecan synthesis in tibial cartilages. Conclusion Low-intensity, low-frequency, and long-duration mechanical loading is the best combination for healthy knee cartilage to maintain homeostasis and activate anabolic responses. Our findings provide a significant scientific basis for exercise and lifestyle instructions.

Description of a new species, Pseudodiscocotyla mikiae n. sp. (Monogenea: Discocotylidae) parasitic on gills of Pristipomoides filamentosus from off Okinawa-jima island in Japan, with redescription of Pseudodiscocotyla opakapaka - Yusuke Kamio; Aina Inoue; Masato Nitta (Systematic Parasitology, 2023)

Correction to: Decline of the chestnut gall wasp population, Dryocosmus Kuriphilus YASUMATSU (Hymenoptera, Cynipidae) after the establishment of Torymus sinensis KAMIJO (Hymenoptera, Torymidae) - Seiichi Moriya; Kouichi Inoue; Akio Ôtake; Masakazu Shiga; Masato Mabuchi (Applied Entomology and Zoology, 2022)

Correlation between cytochrome P450 1A (cyp1a) mRNA expression and ambient phenanthrene and pyrene concentration in Javanese Medaka Oryzias javanicus - Suhaila Rusni; Mieko Sassa; Yusuke Takehana; Masato Kinoshita; Koji Inoue (Fisheries Science, 2020)

Spectrum of mutations and genotype–phenotype analysis in Noonan syndrome patients with RIT1 mutations - Masako Yaoita; Tetsuya Niihori; Seiji Mizuno; Nobuhiko Okamoto; Shion Hayashi; Atsushi Watanabe; Masato Yokozawa; Hiroshi Suzumura; Akihiko Nakahara; Yusuke Nakano; Tatsunori Hokosaki; Ayumi Ohmori; et al. (Human Genetics, 2016)

Genetic similarity of the Hainan medaka populations collected from hyper- and hypo-osmotic environments in northern Vietnam - Hideki Hayakawa; Quang Dung Le; Masato Kinoshita; Yusuke Takehana; Kei Sakuma; Hirohiko Takeshima; Shigeaki Kojima; Kiyoshi Naruse; Koji Inoue (Ocean Science Journal, 2015)

Smad interacting protein 1 (SIP1) is associated with peritoneal carcinomatosis in intestinal type gastric cancer - Yoshinaga Okugawa; Yasuhiro Inoue; Koji Tanaka; Mikio Kawamura; Susumu Saigusa; Yuji Toiyama; Masaki Ohi; Keiichi Uchida; Yasuhiko Mohri; Masato Kusunoki (Clinical & Experimental Metastasis, 2013)

Occurrence of two closely related ricefishes, Javanese medaka (Oryzias javanicus) and Indian medaka (O. dancena) at sites with different salinity in Peninsular Malaysia - Shahrizad Yusof; Ahmad Ismail; Tomoko Koito; Masato Kinoshita; Koji Inoue (Environmental Biology of Fishes, 2012)

Stable isotope and chemical composition of pearls: Biomineralization in cultured pearl oysters in ago bay, Japan - Hodaka Kawahata; Mayuri Inoue; Masato Nohara; Atsushi Suzuki (Journal of Oceanography, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Effect of CYP2D6*10 on pharmacokinetic variability of routinely administered metoprolol in middle-aged and elderly Japanese patients - Masato Taguchi; Takashi Nozawa; Tomoki Kameyama; Hiroshi Inoue; Chihiro Takesono; Akiko Mizukami; Yukiya Hashimoto (European Journal of Clinical Pharmacology, 2003)

Perception of shape-from-motion in macaque monkeys and humans - Shumpei Unno; Reiko Kuno; Masato Inoue; Yasuo Nagasaka; Akichika Mikami (Primates, 2003)

Incomplete replication of human parainfluenza virus type 4 in LLC-MK2 cells and in L929 cells - Hiroshi Komada; Hisae Inoue; Chihiro Yamabayashi; Morihiro Ito; Mitsuo Kawano; Machiko Nishio; Masato Tsurudome; Yuji Kozuka; Naoya Noda; Kazuyoshi Namba; Myles O'Brien; Yasuhiko Ito (Medical Microbiology and Immunology, 2000)